Workshop Peningkatan Pemahaman Konteks pada AKM Numerasi bagi Guru SMP Muhammadiyah 1 Kartasura - Utami, Nida Sri; Swastika, Annisa (Pelita: Jurnal Pengabdian kepada Masyarakat, 2024)
It is hoped that teachers will not only be able to understand, but teachers are also expected to be able to analyze Numeracy AKM questions first. This community service activity aims to increase the understanding of contex of Numeracy AKM for teachers at Muhammadiyah 1 Kartasura Middle School. The methods used in this activity are the speaker give explanation about numeracy AKM, discussion and also training methods. The results obtained from this service activity are that  75% of the teachers understand context of numeracy AKM.